ASYMMETRIC PERIFLEXURAL EXANTHEMA OF CHILDHOOD (APEC) - Anja Kopitar; Mateja Starbek Zorko (Slovenska pediatrija)

(untitled)
Asymmetric periflexural exanthema of childhood (APEC) is a benign, self-limiting skin disease that belongs to the group of parainfectious exanthema. It mainly affects preschool children. The disease is characterised by a unilateral distribution of the rash, which typically begins in the flexor region of the body. The diagnosis is made on the basis of the clinical picture. The disease is usually asymptomatic and resolves spontaneously within 3-6 weeks. No specific treatment or referral to a dermatologist is required. In this article, we present two clinical cases of APEC referred to the outpatient clinic of the Dermatovenerology Clinic in Ljubljana and add basic facts about the dermatosis.